PERANCANGAN DESAIN PERMAINAN MATERI PENDIDIKAN ANAK USIA DINI BERBASIS WAYANG BEBER - Sutedjo, Agus; Prilosadoso, Basnendar Herry (Institut Seni Indoensia Surakarta, 2016)
The traditional game contains a lot of important elements such as aspects of educational, recreational, or competitive so that children can benefit. The traditional game according to the nature ofthe game can be divided into two, namely a game to play (games) that are competitive and games toplay (play) that are available. This study aims to provide solutions related to design problems oftraditional children’s games based material introduction wayang beber in Pacitan and learning media character education for children early age as a way to preserve the traditional art to obtainalternative modification of traditional games. The crisis in various dimensions that many hit Indonesian life that impact on the crisis of morality can be prevented by reviving the character educationthrough the incorporation of traditional games children with puppet figure. Character education isthe transformation of the values of life in one’s personality to become one in the behavior of thatperson’s life. Draft experiment will be conducted with the involvement of a team of professors andstudents and practitioners in the field of craftsmen game and the offender (puppeteer) wayang beber.To map data is done through literature studies, interviews, observation, and documentation. Experiments performed with the shape design and game design approach is supported by the psychologicalapproach, educational, social and cultural. The use of SWOT analysis models used when going to theformulation of traditional game design as a medium for the introduction of the figure of wayangbeber and learning material character education to early childhood.Keywords: Wayang beber Pacitan, the character of early childhood education, traditional games,Art Tradition Preservation.